Problematics of Decentralization in the Field of Health Law in the Autonomous Era - taufik,, Iqbal; Baranyanan, Soeleman Djaiz; Irham, Muhammad (Faculty of Law, Universitas Pekalongan, 2024)
Based on positive law, which applies in Indonesia, decentralization has